2013
DOI: 10.1002/dvdy.24043
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of sexually dimorphic neurogenesis in the Caenorhabditis elegans ventral cord by Hox and TALE homeodomain transcription factors

Abstract: COVER PHOTOGRAPH: Pseudocolored array of C. elegans L1 larvae overexpressing the midbody Hox reporter, lin‐39::lacZ. From Patterning of sexually dimorphic neurogenesis in the Caenorhabditis elegans ventral cord by Hox and TALE homeodomain transcription factors; Kalis, et al, Developmental Dynamics 243:159–171.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In addition, as amply demonstrated in the past, neurotransmitter identity serves as a useful entry point to study mechanisms of neuronal identity control (e.g., Lints and Emmons 1999;Sze et al 2002;Flames and Hobert 2009;Serrano-Saiz et al 2013;Kalis et al 2014;Zhang et al 2014;Pereira et al 2015;Gendrel et al 2016). We anticipate that our neurotransmitter atlas, summarized in Figure 8, will provide further entry points into studying neuron identity control.…”
Section: Sexual Dimorphisms In Neurotransmitter Usage In Sexshared Nementioning
confidence: 80%
See 1 more Smart Citation
“…In addition, as amply demonstrated in the past, neurotransmitter identity serves as a useful entry point to study mechanisms of neuronal identity control (e.g., Lints and Emmons 1999;Sze et al 2002;Flames and Hobert 2009;Serrano-Saiz et al 2013;Kalis et al 2014;Zhang et al 2014;Pereira et al 2015;Gendrel et al 2016). We anticipate that our neurotransmitter atlas, summarized in Figure 8, will provide further entry points into studying neuron identity control.…”
Section: Sexual Dimorphisms In Neurotransmitter Usage In Sexshared Nementioning
confidence: 80%
“…subclassification does not correlate with the connectivity-based classification of "response rays" and "PVV rays" (Jarrell et al 2012). Neurotransmitter diversity is also seen in the CP ventral cord neuron class, which was reported to be distinct based on connectivity and patterns of serotonin and neuropeptide usage (Loer and Kenyon 1993;Jarrell et al 2012;Kalis et al 2014). The subclass-specific usage of Glu and GABA as well as the differential expression of unc-47/VGAT and unc-17/VACHT in subsets of CP neurons that we report here further corroborates a subclass diversification into at least six distinct subclasses (CP0, CP01-04, CP05-06, CP07, CP08, and CP09; Table S1).…”
Section: Neuronal Subclasses Express Distinct Neurotransmittersmentioning
confidence: 95%
“…The regulatory mechanisms that implement this sexual dimorphism in lineage and cell fate remain largely unclear. Several factors contribute to patterning and fate specification in both sexes, including the Hox genes lin-39 and mab-5, and the TALE-homeodomain transcription factor genes unc-62 and ceh-20 (Clark et al 1993;Salser et al 1993;Liu et al 2006;Potts et al 2009;Kalis et al 2014). It seems likely that TRA-1A acts together with these and other factors in the ventral hypodermis to control its sexually dimorphic development.…”
Section: Sex-specific Neurogenesis: Regulation Of Cell Lineage and DImentioning
confidence: 99%
“…UNC-62, along with LIN-39, promotes survival of the VCs by ensuring CEH-20 localizes to the nucleus; the LIN-39/CEH-20 complex then represses egl-1 transcription (Liu et al 2006;Potts et al 2009). Sexual determination of the Pn.aap cells is established by the first larval (L1) stage (as VCs in hermaphrodites and the precursors of CAs and CPs in males) (Kalis et al 2014). It was also shown that LIN-39 is not required for the expression of the VC terminal differentiation feature ida-1.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, since the surviving descendants from P1, P2, and P9-12 still express ida-1::gfp in lin-39(lf); ced-3(lf) double mutants, it was concluded that the role of LIN-39 is most likely restricted to VC survival, not differentiation (Kalis et al 2014). However, recent evidence has implicated a role for LIN-39 in the expression of a VC marker srb-16 (Feng et al 2020).…”
Section: Introductionmentioning
confidence: 99%